Voice evaluation – contribution of the speech-language pathologist voice specialist – SLP-V: part B. Acoustic analysis, physical examination and correlation of all steps with the medical diagnoses. (3rd December 2021) - Behlau, Mara; Madazio, Glaucya; Vaiano, Thays; Pacheco, Claudia; Badaró, Flávia
Abstract: This article describes the contribution of the speech-language pathologist, voice specialist SLP-V in the assessment of patients with voice problems. Part B explores acoustic analysis to measure the vocal signal and to produce comprehensive documentation of the patient; the physical examination to assess the involvement of body tension, including the larynx, cervical muscles, and breathing pattern; and finally, the correlation of all previously described steps to make a clinical decision combining the patient information, tests performed, and the physical examination of the individual. Worldwide published tendencies and specific comments of each step highlight the role of the SLP-V.